Human Resources Management (HRM) Practices and Service Quality in Selected Insurance Companies in Nigeria - Shola, Ahmodu Tijani Ismail; Adnan, Zurina; Saad, Shahrin (2017)
Human Resources Management (HRM) practice shows a key function in customer satisfaction in the cognitive of service quality in selected insurance companies in Nigeria. The significant of service industries are labour oriented where insurance sector is not an exception because their performance is determined by the quality of risk management services to their customers (Insured). Human Resources serve as the key imperative asset for any organization and development of the service quality in Nigeria insurance industry by improving its service based on effectiveness, efficiency, customer relationship and ethical practices.Purpose: This paper is aimed to investigate Human Resources Management Practices and Service quality in selected insurance companies in Nigeria.Methodology: The study adopts secondary data which reviews related literatures from journal articles and other literatures on assessment of the concepts.Finding: The paper finds that there is significant relationship between Human resources management practices and service quality in insurance industry.It also reveals that Human resources management practices directly affect overall service quality in terms of customer base, customer retention, overall profit, productivity and risk improvement to the customers. Implication: Organization having good HRM Practices will improve the quality of services provided and also improves performance and customers’ loyalty.